Lithium isotopes in marine food webs: Effect of ecological and environmental parameters - Thibon, Fanny; Weppe, Lucas; Churlaud, Carine; Lacoue-Labarthe, Thomas; Gasparini, Stéphane; Cherel, Yves; Bustamante, Paco; Vigier, Nathalie (Frontiers in Environmental Chemistry, 2023)
Non-conventional stable isotopes have received increasing attention in the past decade to investigate multi-level ecological connections from individuals to ecosystems. More recently, isotopes from trace and non-nutrient elements, potentially toxic (i.e. Hg), have also been recognized of great significance to discriminate sources, transports, and bioaccumulation, as well as trophic transfers. In contrast, lithium (Li) concentrations and its isotope compositions (δ7Li) remain poorly documented in aquatic ecosystems, despite its possible accumulation in marine organisms, its increasing industrial production, and its demonstrated hazardous effects on biota. Here, we present the first Li isotope investigation of various soft tissues, organs or whole organisms, from marine plankton, bivalves, cephalopods, crustaceans, and fish of different biogeographical regions (North Mediterranean Sea, North Atlantic Ocean (Bay of Biscay), South East Pacific Ocean (New Caledonia), and Southern Indian Ocean (Kerguelen Islands)). Independently of the considered organisms, δ7Li values range widely, from 4.6 ‰ (digestive gland of bivalves) to 32.0 ‰ (zooplankton). Compared to homogeneous seawater (δ7Li ~ 31.2 ± 0.3 ‰), marine organisms mostly fractionate Li isotopes in favor of the light isotope (6Li). Within the same taxonomic group, significant differences are observed among organs, indicating a key role of physiology on Li concentrations and on the distribution of Li isotopes. Statistically, the trophic position is only slightly related to the average Li isotope composition of soft tissues of marine organisms, but this aspect deserves further investigation at the organ level. Other potential influences are the Li uptake by ingestion or gill ventilation. Overall, this work constitutes the first δ7Li extensive baseline in soft tissues of coastal organisms from different large geographic areas mostly preserved from significant anthropogenic Li contamination.